2019
DOI: 10.1093/cid/ciz1097
|View full text |Cite
|
Sign up to set email alerts
|

Liver Fibrosis Progression and Mortality in Hepatitis B– and C–Coinfected Persons Treated With Directly Acting Antiviral Agents: Results From ERCHIVES

Abstract: For persons with baseline Fibrosis-4 1.46–3.25, cirrhosis incidence/1000 patient-years was 49.3 among hepatitis B virus (HBV)/hepatitis C virus (HCV) coinfected and 18.2 among HCV monoinfected (P = .03). Cirrhosis risk was numerically higher but statistically nonsignificant among HBV/HCV coinfected (hazards ratio [HR] 1.51; 95% confidence intervals [CI], .37–6.05) but lower among those who attained sustained virologic response (HR, .52; 95% CI, .42–.63).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Multivariable logistic regression analysis was used to generate odds ratios and 95% confidence intervals for factors associated with attainment of SVR. Variables were included based on their known association with HCV virologic response and our previous published studies that have used similar variables (Butt et al, 2019a;Butt et al, 2019b;Butt et al, 2019c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multivariable logistic regression analysis was used to generate odds ratios and 95% confidence intervals for factors associated with attainment of SVR. Variables were included based on their known association with HCV virologic response and our previous published studies that have used similar variables (Butt et al, 2019a;Butt et al, 2019b;Butt et al, 2019c).…”
Section: Discussionmentioning
confidence: 99%
“…We used the Electronically Retrieved Cohort of HCV Infected Veterans (ERCHIVES) for the current study. ERCHIVES has been detailed in numerous previous publications (Butt et al, 2019a;Butt et al, 2019b;Butt et al, 2019c). Briefly, all Veterans in the Department of Veterans Affairs healthcare system (VA) who were diagnosed to have HCV based on an positive HCV antibody test are included in the cohort.…”
Section: Study Populationmentioning
confidence: 99%
“…When the injury is removed, activated HSCs (myofibroblasts) are reduced through deactivation or apoptosis to slow down the fibrotic process and even lead to regression. Studies have shown that patients with chronic hepatitis B or chronic hepatitis C have reduced liver fibrosis after receiving antiviral therapy[ 74 ]. In addition, therapies such as antioxidants, renin–angiotensin system inhibitors, and traditional Chinese medicine[ 75 ] are also considered promising for treatment of liver fibrosis, although more clinical trials are needed to confirm their safety and efficacy.…”
Section: Potential Application Of Ncrnas For the Treatment Of Liver F...mentioning
confidence: 99%
“…A recent study reported on whether the clearance of HCV by DAA could improve the clinical outcomes of co-infected patients [32]. For persons with baseline significant fibrosis, as indicated by a FIB-4 score of 1.46-3.25, cirrhosis incidence was 49.3/1000 patient-years among 151 HCV/HBV co-infected patients and 18.2 among HCV mono-infected patients (p = 0.03).…”
Section: Daa-based Therapymentioning
confidence: 99%